PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI, STRUKTUR MODAL DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KELUARGA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 201 - Endang Wahyuni; Endang Purwaningsih (STIE St. Pignatelli Surakarta, 2021)
This study aims to provide empirical evidence regarding the effect of managerial ownership, firm size, profitability, dividend policy, investment decisions, capital structure and intellectual capital on firm value. The population of this study is family companies listed on the Indonesia Stock Exchange during 2016-2019. The sample of this research is 128 samples. Sampling using purposive sampling method, namely determining the sample from the existing population based on the criteria desired by the researcher. This study uses multiple linear regression to analyze the data. The results of this study indicate managerial ownership has no effect on firm value, firm size has no effect on firm value, profitability has a significant positive effect on firm value, dividend policy has no effect on firm value, investment decisions have a significant positive effect on firm value, capital structure has a significant negative effect on firm value, and intellectual capital has no effect on firm value.